Immunoadjuvant Nanoparticles as Trojan Horses for Enhanced Photo-Immunotherapy in the Treatment of Triple-Negative Breast Cancer - Jinxian Wu; Jinxian Wu; Shanyong Wang; Shanyong Wang; Shanshan Liu; Shanshan Liu; Fang Liu; Fang Liu; Feifan Zhou; Feifan Zhou (Frontiers in Pharmacology, 2022)
Treatment of triple-negative breast cancer (TNBC) faces great challenges due to high invasiveness and poor prognosis. Therefore, effective treatment methods are urgently needed to control primary tumors and suppress distant tumors. Herein, we employed glycated chitosan (GC), a polysaccharide macromolecular immunoadjuvant, to construct a self-assembly GC@ICG nanoparticle which is accessible to tumor cells for synergistic cancer treatment based on the combination of phototherapy and immunotherapy. In this strategy, the self-associated synthesis of spherical GC@ICG significantly improved the stability of ICG and endowed GC with Trojan Horses in tumor cells to enhance tumor immunogenicity. A bilateral 4T1 tumor-bearing mouse model was established to evaluate the therapeutic outcomes and specific host antitumor immune response. Finally, GC@ICG-based phototherapy can directly eliminate primary tumors and resist the progression of untreated distant tumors. In addition, compared to the treatment of L + GC + ICG, GC@ICG-based phototherapy was evidenced to suppress lung metastasis and enhance infiltration of CD8+ T cells in untreated distant tumors. Therefore, this design shows promise in addressing the challenges of the treatment of TNBC.